A DECONSTRUCTIVE READING OF MITCH ALBOM’S TUESDAYS WITH MORRIE - Pioro Benevolent Lariesto (Muse: Jurnal of Art, 2024)
The novel Tuesdays with Morrie conveys people way to value life even though in bitterness and sadness. These values of life are taught by Morrie, a professor who is dying because of his disease Amyotrophic Lateral Sclerosis (ALS). In his last breath, he is never afraid of death and he accepts his life without complains and regrets. He keeps on having good spirit, does his best, never changes and be a motivator for many people especially for Mitch. This is library research where all data are taken from the library and internet browsing. This research applies the deconstructive Theory proposed by Jacquess Derrida in order to find the Binary Opposition and the hierarchy of meanings contained within the novel. It is concluded that from the two binary opposition that has been analysed that there is a fluidity and instability of system of meaning in the novel.